Detection of Lead Using a Sensitive Anodic Stripping Voltammetric Method Based on Composite Mesoporous Silica/Bismuth Oxychloride Modified Electrode. Issue 8 (27th February 2018) - Song, Yiyan; Jiang, Huijun; Shi, Xueyan; Chen, Jin; Wu, Yuan; Wei, Wei
Abstract: Exposure to lead in the environment and food poses severe threat to human health especially for the nervous and hemopoietic system, of which children are more vulnerable than adults. In this study, a sensitive detection platform aimed at the blood lead sample was developed based on BiOCl‐KIT‐6 composite materials modified glassy carbon electrode (BiOCl‐KIT‐6/GCE). The BiOCl‐KIT‐6 composites of varied molar ratio of Bi/Si with a litchi‐like surface structure are facilely prepared under hydrothermal conditions. The synthesized composites and modified electrode were characterized by a combination of physicochemical as well as electrochemical methods. Under optimized experimental conditions, square wave anodic stripping voltammetry (SWASV) was employed to determine the lead concentration using BiOCl‐KIT‐6/GCE, which exhibits a good electrochemical response to Pb (II) with linear calibration curves ranging from 0.2 to 10 and 10 to 300 μg/L and a detection limit of 33 ng/L. The constructed sensor was also successfully used for the electrochemical determination of lead‐spiked human blood sample with desirable accuracy. Abstract : The glassy carbon electrode modified with mesoporous composite of litchi‐like bismuth oxychloride on sileceous support exhibits a good electrochemical response to Pb (II) with linear calibration curves ranging from 0.2 to 10 and 10 to 300 μg/L and a detection limit of 33 ng/L, which is also successfully used for the electrochemical determination of lead‐spiked human blood sample with desirable accuracy.